Effect of pseudorotation on isochoric thermal conductivity of hydrocarbons in disordered phases - Sagan, V.V.; Konstantinov, V.A.; Revyakin, V.P.; Karachevtseva, A.V. (Recent Contributions to Physics, 2015)
The isochoric thermal conductivity of solid five-membered heterocyclic compounds has been measured in orientationally ordered and orientationally disordered («plastic») phases on samples of different density in a wide interval of temperatures and pressures. The objects were: furan – C4H4O, cyclopentane – C5H10, thiophene – C4H4S. The aim of this research was to study the influence of the translation-orientational motion on the behavior of the isochoric thermal conductivity and to estimate the possible contribution of pseudorotation to the total heat transfer.